Measurements of air-sea gas transfer velocities in the Baltic Sea - Nagel, Leila; Krall, Kerstin Ellen; Jähne, Bernd (Ocean science, 2019)
Heat transfer velocities measured during three different campaigns in the Baltic Sea using the active controlled flux technique (ACFT) with wind speeds ranging from 5.3 to 14.8 m s−1 are presented. Careful scaling of the heat transfer velocities to gas transfer velocities using Schmidt number exponents measured in a laboratory study allows us to compare the measured transfer velocities to existing gas transfer velocity parameterizations, which use wind speed as the controlling parameter. The measured data and other field data clearly show that some gas transfer velocities are much lower than those based on the empirical wind speed parameterizations. This indicates that the dependencies of the transfer velocity on the fetch, i. e., the history of the wind and the age of the wind-wave field, and the effects of surface-active material need to be taken into account.